Delayed-Onset Bilateral Vocal Cord Paralysis After Abdominal Surgery: A Case Report. Issue 12 (15th June 2018) - Kotoda, Masakazu; Oguchi, Takeshi; Takamino, Ayasa; Wada, Keiichi; Matsukawa, Takashi
Abstract : A 62-year-old male patient suddenly developed severe dyspnea due to bilateral vocal cord paralysis (VCP) 4 days after an abdominal surgery. Emergent tracheostomy effectively improved the patient's respiratory status. The present case report emphasizes that bilateral VCP could occur even several days after an abdominal surgery in patients with multiple risk factors, such as hypertension, diabetes mellitus, an older age, male sex, and an upper abdominal surgery. Even if the patient does not present with hoarseness, bilateral VCP should not be ruled out, because a slight phonetic change can be the only symptom of early-stage bilateral VCP.